Real-world evidence of treatment for relapse of noninfectious uveitis in tertiary centers in Japan: A multicenter study. Issue 9 (March 2019) - Takeuchi, Masaru; Kanda, Takayuki; Kaburaki, Toshikatsu; Tanaka, Rie; Namba, Kenichi; Kamoi, Koju; Maruyama, Kazuichi; Shibuya, Etsuko; Mizuki, Nobuhisa
Abstract : Abstract: Noninfectious uveitis (NIU), which pathogenesis is often autoimmune nature, occurs as a symptom of systemic syndromes or only in the eye. The standard treatment of NIU is local, topical, and oral administration of corticosteroids (CS) in combination with immunomodulatory therapy (IMT). However, additional therapeutic strategies involving topical and systemic administration of CS or others to treat relapse or exacerbation of ocular inflammation in NIU which present as various ocular manifestations have not been established. The aim of this study was to investigate therapeutic strategies used for various ocular inflammations in relapse or exacerbation of NIU and to evaluate factors associated with the treatment pattern in Japan. The subjects were 198 eyes of 156 NIU patients with relapse or exacerbation of ocular inflammation at 6 university hospitals in Japan. The most frequent disease was sarcoidosis in 23.7% of the cases, followed by Behçet disease (BD) in 21.2%, Vogt-Koyanagi-Harada (VKH) disease in 13.6%, acute anterior uveitis (AAU) in 5.6%, tubulointerstitial nephritis and uveitis syndrome (TINU) in 4.0%, and juvenile idiopathic arthritis (JIA)-associated uveitis in 3.0%. Common ocular findings were worsened anterior inflammation (AI) in 67.2% of the cases, vitreous opacity (VO) in 46.5%, macular edema (ME) in 26.8%, retinal vasculitis (RV) in 23.7%, serous retinal detachment (SRD) in 9.1%, and optic perineuritis (OPN) in 4.0%. Reinforcement of betamethasone eye drop (ED) monotherapy for only AI in both unilateral and bilateral AI, sub-tenon injection of triamcinolone acetonide (STTA) for unilateral posterior inflammation including VO and ME, and systemic therapy using CS and/or IMT for bilateral anterior and posterior inflammation were significantly more frequent. Frequencies of exacerbated individual ocular findings in sarcoidosis and BD were similar, and severe ocular inflammation associated with panuveitis required both topical and systemic therapies. These results demonstrate that reinforcement of betamethasone EDs, topical administration of triamcinolone acetonide, and long-term administration of systemic corticosteroids are the major therapeutic strategies, and reinforcement of betamethasone EDs was used for exacerbated AI independently from its use for posterior inflammation. In addition, STTA was preferentially used for VO and ME associated with posterior inflammation.